International ranking systems and their relevance for the Research performance assessment of universities: A case study of university of Jaffna - Janen, T. (University Librarians Association of Sri Lanka, 2023)
This study aimed to explain the relevance of international ranking systems in assessing the research performance of universities. Research publication details of University of Jaffna were retrieved from the annual reports, Scopus database and Web of Science database from the year 2020 to 2022. Furthermore, the research delves into popular international ranking systems and their indicators and weightage, that impact the research ranking of an academic institution. The University of Jaffna published more journal articles (252) and conference articles (601) in 2021 than in other years considered for this study. According to the annual report, University of Jaffna published 29.31% of journal articles during the three years among the total publications. In 2020, 43.38% of the journal articles were published in Scopus followed by 40.47% in 2021 and 48.77% in 2022. Since, THE world university ranking, QS ranking and SCImago ranking rely on Scopus database, these ranking systems considered only 43.38%, 40.47% and 48.77% of research publications during 2020, 2021 and 2022 respectively to measure the University of Jaffna research-related indicators. URAP ranking considered 28.57%, 27.38% and 29.09% of the total University of Jaffna publications for the ranking. Webometric considered the Google profile details of the research publications, which include only the institutional email ID profile research publications. Nearly 59.13% of the staff have their Google profiles under institutional profile, which contribute to webometric ranking. This study revealed that less than 50% of the research output was considered by the popular international ranking systems to measure the research-related indicators of University of Jaffna. It is because of data sources used by the ranking systems. Further, this study explained that, the popular ranking systems failed to use holistic approach to measure the research performance of the University of Jaffna and discussed the shortcoming in methodology follow and transparency. Ranking numbers of higher education institutes may have impact on policy making and the policy makers should consider the shortcoming when these were used as information source. Also, it recommended that, a national level ranking can be developed to measure the performance of higher education institutes by considering specific needs and objectives of the higher education institutes rather than relying solely on the international ranking systems.
Keywords: International ranking systems; Research performance; University of Jaffna; Higher education institutions